Synthesising causal loop between environmental and compound droughts: A systems-driven framework for climate-resilient governance in monsoon-sensitive agroecosystems - Aman Srivastava; Rajib Maity; Venkappayya R. Desai (Next Sustainability, 2025)
Conventional drought indices, which focus on isolated systems (meteorological, agricultural, hydrological), struggle to capture cross-system feedbacks, leading to fragmented policymaking and heightened cascading risks. This study introduces a novel systems-driven framework that integrates three key components: (1) the Environmental Drought Index (EDI), facilitating the inclusion of environmental flow deficits within compound drought assessments to complement traditional drought indices; (2) the Entropy-based Compound Drought Index (ECoDI), which combines conventional drought indices [Standardized Precipitation Evapotranspiration Index (SPEI), Standardized Soil Moisture Index (SSMI), Standardized Streamflow Index (SSI)] with EDI using Shannon entropy weights to emphasize signals with high informational variability; and (3) the joint application of Causal Loop Diagrams (CLDs) and the Cross-Index Synergy Matrix (CISM) to bridge drought science and governance. CLDs illustrate nonlinear feedbacks, while the CISM (a newly developed dual-matrix approach) translates ECoDI/EDI severity tiers into adaptive policy recommendations. Applied to the Jaraikela catchment in India’s Brahmani River basin, the framework highlights temporal mismatches in drought propagation (1982–2023), such as the rapid transition from meteorological to agricultural drought (lag of 1–2 months), the delayed onset of hydrological drought (lag of 2–4 months), and the persistence of environmental droughts (lag of 1–3 months after hydrological drought). The analysis identifies major drivers, including the impact of agricultural withdrawals on environmental flows and the effect of delayed monsoon onset on soil moisture deficits. Validation against the Vegetation Health Index (R=0.873, AUC-ROC=0.84) demonstrates ECoDI’s effectiveness in detecting compound drought events and capturing post-2000 intensification trends. By embedding entropy-weighted monitoring into decision-making, the approach supports improved drought governance, operationalizing EDI/ECoDI thresholds through a tiered governance matrix (CISM), and recommending context-specific interventions.